Pentingnya Mediasi Dalam Penyelesaian Sengketa di Pengadilan Agama Kisaran - Suryawan, Ari; Meliala, Philip Rio; Lubis, Sofyan Soury (Al-Hayat: Natural Sciences, Health & Environment Journal, 2023)
The purpose of this research is to find out how mediation exists in resolving disputes in the Kisaran Religious Courts and aims to analyze the effectiveness of Supreme Court Regulation Number 1 of 2016 regarding the Implementation of Divorce Mediation in the Kisaran Religious Courts as well as to find out the factors that hinder the effectiveness of the Court Regulations. Agung Number 1 of 2016 at the Sengkang Religious Court. This research was carried out at the Kisaran Religious Court. The research method used is field research with data collection techniques, namely interviews and documentation and analyzed qualitatively. The results of the research show that the effectiveness of Supreme Court Regulation Number 1 of 2016 has not been implemented effectively because it has not been implemented optimally because the comparison of cases each year with the success of mediation is far different. The factors that hinder the effectiveness of Supreme Court Regulation Number 1 of 2016 regarding the implementation of divorce mediation at the Sengkang Religious Court are internal factors, namely the quantity of cases due to the large number of cases being handled at the Sengkang Religious Court and external factors, namely the support of legal counsel where legal counsel is lacking. encourage the parties to undertake the mediation process. Keywords: Mediation, Dispute, Court.